Measuring the immeasurable: a survey of substainability indices - Christoph Böhringer; Patrick Jochem (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Sustainability indices for countries provide a one-dimensional metric to valuate country-specific information on the three dimensions of sustainable development: economic, environmental, and social conditions. At the policy level, they suggest an unambiguous yardstick against which a country?s development can be measured and even a cross-country comparison can be performed. This paper reviews the explanatory power of various sustainability indices applied in policy practice. We show that these indices fail to fulfill fundamental scientific requirements making them rather useless if not misleading with respect to policy advice.
Keywords: Q01; C43; 330; Sustainability Indices; Composite Indicators; Sustainability; Indices